The use of 'Think-Out-Loud' methodology in the development of teaching materials for abbreviated breast Magnetic Resonance Imaging scan (FAST MRI) interpretation, and a comparison of the learning experience of two reader cohorts. (2019) - Harding, Sam; Geach, Rebecca; Jones, Lyn; ,
Abstract: Aim: FAST MRI is an abbreviated breast MRI technique, proposed as a screening tool for breast cancer. This study aims to explore how 'Think-Out-Loud' (TOL) methodology can effectively develop and shape training to interpret standard breast MRI on readers' learning experience. Materials and methods: TOL methodology asks people to speak their thoughts while performing a task; to say whatever they are looking at, thinking, doing, and feeling at each moment. It helps determine expectations and identify aspects of confusion. This methodology was adopted with two groups of image readers to develop training materials for FAST MRI interpretation. Eight image readers (readers); 4 NHS Breast Screening Programme (NHSBSP) breast MRI and mammogram readers (Group 1) and 4 NHSBSP mammogram readers who do not read breast MRI (Group 2) were audio and video recorded during training. Content analysis was undertaken. Results: TOL was well received by the readers and allowed iterative development and refinement of a training package. Challenges relating to introducing new concepts and managing uncertainty were identified through the analysis of the TOL audio data. Additionally, Group 2 asked for more clarification than Group 1, of both the teaching materials and how to use the image-manipulation software. Conclusion: TOL methodology allowed effective training of both groups of readers. The iterative nature of individual training ensured production of user-friendly materials including frequently-asked-questions sheets. It allowed for each person to feel that their views were fully listened to and incorporated into the training package, allowing for training materials with high face validity.